The Function of the Nyadran Dam Bagong Tradition in Trenggalek Regency: William R. Bascom's Theory - Ayu Safitri, Niken Diah; Maulfi Syaiful Rizal (Universitas Negeri Semarang, 2024)
The Trenggalek people have a tradition that is used as local wisdom, namely the Nyadran Dam Bagong tradition which is very attached to its history. This tradition is used as a research object with a study focus on cultural history, pamali, and the function of its traditions. The theory used in this research is William R. Bascom's theory of function, namely as a form of entertainment, a means of validating cultural institutions and institutions, a tool for educating children, and a tool for coercion or supervision so that community norms are adhered to. The method in this research is qualitative descriptive research with an oral literature approach. The data sources in this research are the caretaker as informant, recordings and notes during the research and documents. The data in this research are the cultural history, pamali, and function of the Nyadran Dam Bagong tradition in Trenggalek Regency. Data collection in this research was carried out using observation and interview techniques. The data analysis used in this research is content analysis and descriptive analysis. The results obtained from this research are a description of the cultural history, pamali, and function of the Nyadran Dam Bagong tradition in Trenggalek Regency according to William R. Bascom's function theory, namely as a form of entertainment, a means of ratifying cultural institutions and institutions, a tool for children's education, and a tool coercor or supervisor so that community norms are adhered to.